(untitled) (Journal of Medicine, 2019)
Background: Stroke in young age is less frequent than in older populations but has a major impact on the individual and society. This study was done to find out aetiological pattern and associated risk factors of stroke in young adults. Methods: This descriptive cross-sectional observational study was conducted in the Department of Medicine and Neurology, Dhaka Medical College, Dhaka, during the period of April to October 2016. We studied consecutive 100 stroke patients between the age of 15-45 years. Results: In this study 62% patients were male and 38% were female, male incidence is 24% higher than female and ratio is 1. 38. Infarction was found in 65% cases. Haemorrhage was in 35% cases. Dyslipidaemia was mostly associated risk factor in both infarction (76. 91%) and in haemorrhage (85. 71%). High prevalence of dyslipidaemia as associated risk factor may indicate premature atherosclerosis. Conclusion: Stroke in young requires a different approach to investigation and management than stroke in the elderly due to differences in the relative frequencies of possible underlying causes. It remains the case, however, that atherosclerosis contributes to a large proportion of stroke in young patients, thus conventional risk factors must be targeted aggressively. J MEDICINE JAN 2020; 21 (1) : 26-30